2009
DOI: 10.1002/jclp.20586
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder behaviors and depression: a minimal relationship beyond social comparison, self‐esteem, and body dissatisfaction

Abstract: Existing literature fails to comprehensively identify factors contributing to the comorbid relationship between eating disorder (ED) behaviors and unipolar depression. Maladaptive social comparison, body dissatisfaction, and low self-esteem are disruptive psychological patterns common to both constructs. It is unclear whether a unique relationship exists between depression and eating disorder behaviors beyond the effects exerted by this negative cognitive triad. The purpose of the present study is to examine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 42 publications
0
28
1
1
Order By: Relevance
“…In adult samples Cronbach's alpha ranged from .80 to .88 (Corning et al 2006;Hawkins et al 2004;Shahani et al 1990). In a college sample the RSES correlated inversely with body dissatisfaction (Pearson's r=−.30), eating disorder symptoms (r=−.37), and depression (r=−.36), demonstrating evidence of construct validity (Green et al 2009). Cronbach's alpha for the current sample was .91 (heterosexual men=.89; bisexual men=.90; gay men=.90; heterosexual women=.92; bisexual women=.92; lesbian women=.89).…”
Section: Self-esteemmentioning
confidence: 96%
See 1 more Smart Citation
“…In adult samples Cronbach's alpha ranged from .80 to .88 (Corning et al 2006;Hawkins et al 2004;Shahani et al 1990). In a college sample the RSES correlated inversely with body dissatisfaction (Pearson's r=−.30), eating disorder symptoms (r=−.37), and depression (r=−.36), demonstrating evidence of construct validity (Green et al 2009). Cronbach's alpha for the current sample was .91 (heterosexual men=.89; bisexual men=.90; gay men=.90; heterosexual women=.92; bisexual women=.92; lesbian women=.89).…”
Section: Self-esteemmentioning
confidence: 96%
“…Gender role orientation, social comparison, self-esteem, and body dissatisfaction were entered as predictors of eating symptoms for all groups while controlling for BMI, age, exercise frequency, and income in hierarchical regression analyses. All selected variables are empirically supported correlates of eating disorder symptoms (see Ålgars et al 2009;Brown and Graham 2008;Green et al 2009;Heatherton et al 1997;Hospers and Jansen 2005;Lakkis et al 1999;Meyer et al 2001;Wood 2004).…”
Section: Present Studymentioning
confidence: 99%
“…In contrast, eating disordered behavior may be largely triggered by negative emotional experiences, such as feelings of sadness, loneliness, and dissatisfaction with current circumstances. Indeed, social comparison, low self-esteem, and Body Dissatisfaction have been found to account for much of the variance in explaining eating disordered behaviors (Green et al, 2009). Further research is needed to explain the relationship between OCD, depression, and eating pathology.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in the case of EDs and depression, comorbidity rates describe the percentage of a given population that meets criteria for both disorders. Research suggests that EDs and depression are highly comorbid [9-11]. For instance, Green and colleagues found that lifetime prevalence rates of major depression in patients diagnosed with EDs ranged from 36% to 86% [9].…”
Section: Reviewmentioning
confidence: 99%